Do saber ao agir : uma reflexão sobre o diálogo entre ciências da natureza e teologia para alicerçar uma ação em vista do futuro do planeta e a contribuição da teologia da trindade criadora de Jürgen Moltmann - Oliveira, Eliseu Lucas Alves de (2021)
This paper has like theme the dialogue between Theology and Natural Science, to value the differences and the possibilities of closely, aiming to do an alliance in the commun work by future in the planet life, that is threatened. For this, the, it will be valued in two methodologies, in is diferences and similarities, Where is mentioned two charecters: Galileu and Abraão, They representat two diferente looks, those complete each other. The reflection will culminate with on Trinitarian Doctrine of Moltmann Creation, that affirms the transcendence and immanence of God in history, leading it, not a catastrophe, but to full carrying.